2019
DOI: 10.3390/cancers11101443
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Routine TERT Promoter Mutational Screening of Follicular Thyroid Tumors of Uncertain Malignant Potential (FT-UMPs): A Useful Predictor of Metastatic Disease

Abstract: Mutations of the Telomerase reverse transcriptase (TERT) gene promoter are recurrently found in follicular thyroid carcinoma (FTC) and follicular tumors of uncertain malignant potential (FT-UMP), but nearly never in follicular thyroid adenoma (FTA). We, therefore, believe these mutations could signify malignant potential. At our department, postoperative TERT promoter mutational testing of FT-UMPs was implemented in 2014, with a positive mutation screening leading to vigilant follow-up and sometimes adjuvant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…Recent studies have reported the feasibility of TERT promoter mutation detection and its applicability in screening programs for patients with thyroid cancer to predict patient's outcome (21,23). Our study suggests that in head and neck tumors, TERT promoter mutations could be performed in a screening setting to help clinicians decide for a more aggressive initial treatment accompanied by a closer follow-up, in order to give these patients a better chance to survive.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recent studies have reported the feasibility of TERT promoter mutation detection and its applicability in screening programs for patients with thyroid cancer to predict patient's outcome (21,23). Our study suggests that in head and neck tumors, TERT promoter mutations could be performed in a screening setting to help clinicians decide for a more aggressive initial treatment accompanied by a closer follow-up, in order to give these patients a better chance to survive.…”
Section: Discussionmentioning
confidence: 76%
“…TERT promoter mutation has been extensively evaluated in different tumors: thyroid, glioblastoma, urothelial, melanoma, among others (20). Literature reports the use of TERT promoter mutation screening programs in thyroid tumors in order to select patients who would benefit from adjuvant treatment and closer follow-up (21), since many studies related the presence of these mutations with poor prognosis (22)(23)(24)(25). Glioblastomas also are reported to present a poor prognosis in patients harboring TERT mutations, which were commonly evaluated in combination with IDH and MGMT methylation (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Other works have also analysed the role of TERTp mutations as a predictor of the disease, where they report a frequency of 39% in atypical FTAs, also designated 'follicular tumour of uncertain malignant potential' (FT-UMPs) [30]. In accordance, Hysek et al reported that TERTp mutated FT-UMPs harboured malignant potential and exhibited similar recurrences rates as TERTp mutated minimally invasive FCTs [31]. Our group reported the presence of these mutations in a radiation context, in which TERTp mutations were detected in 12% of carcinomas and in 21% of adenomas; the mutational profile is different in the latter, being the most frequent alterations the c.1−146C > T and the c.1−124/−125CC > TT tandem mutation.…”
Section: Introductionmentioning
confidence: 89%
“…Previous efforts to determine the genomic profile of invasive FTC relative to follicular adenoma or minimally invasive tumors have been largely unsuccessful, in part due to the heterogeneity of oncogenic drivers in follicular thyroid tumors [4,8,9]. A reliable marker for universal reflex screening is therefore not yet available for use in clinical practice, although some markers do show promising value in this context [15,16]. In this background, our group performed expression profiling of selected transcription factors in a cohort of invasive FTC specimens, by qPCR and immunohistochemistry approaches, to investigate a potential invasion-promoting transcriptional switch.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from our group profiled the genetic landscape of miFTC, eaFTC, and wiFTC; no definitive genetic predictors of invasion were identified, although mutational burden was shown to be an important predictor of prognosis independent of histological classification [4]. Moreover, recurrent mutations of the TERT promoter are found in subsets of FTCs with particular poor prognosis, and recent studies have suggested that this mutation might be able to discriminate between malignant and benign follicular thyroid neoplasia [15][16][17][18]. A marker of invasive FTC might serve some function in distinguishing FTC from adenoma but might also provide guidance as to the intensity of therapy or follow-up, which could be quite different for miFTC versus wiFTC.…”
Section: Introductionmentioning
confidence: 97%